Private Activity in Infrastructure Shows Mixed Results in 2005 - World Bank (Washington, DC, 2012)
Investment commitments to infrastructure projects with private participation grew in 2005, but the number of infrastructure projects reaching financial closure fell, according to just-released data from the Private Participation in Infrastructure Database.